How would the expression x^3 - 64 be rewritten using difference of cubes? A. (x + 4)(x^2 - 4x + 16) B. (x-4)(x^2 + 4x + 16) C. (x+4)(x^2 - 4x - 16) D. (x-4)(x^2 + 16x+4)
![How would the expression x3 64 be rewritten using difference of cubes A x 4x2 4x 16 B x4x2 4x 16 C x4x2 4x 16 D x4x2 16x4 class=](https://us-static.z-dn.net/files/d56/7f7593f9066b8610b19eb4d7aa530509.jpg)
Answer:
D)
Step-by-step explanation:
4 is an evident zero of the equation x^3 - 64.
x^3 - 64 can only be factorized with (x-4) and not with (x+4)
because x - 4 = 0 <==> x = 4 and 4^3 -64 = 0
Developing B) would be:
x^3 + 4x^3 + 16x - 4x^2 - 16x - 64 = 5x^3 - 4x^2 -64
So it doesn't match so it's D)